Pricing Strategy for the Organic Eggs: Willingness to Pay and Hedonic Price Approaches - Relawati, Rahayu; Szymoniuk, Barbara; Ariadi, Bambang Yudi; Handayanto, Eko (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Organic eggs have been marketed to provide safe food and protect the environment sustainability all at once. However, the high price is being an obstacle to expanding the organic egg market in East Java Province. The aims of this research were to analyze the factors that influence the willingness to pay (WTP) and hedonic prices of organic eggs and to formulate pricing strategies. This research was conducted by using an online survey method in East Java Province, Indonesia. The survey was conducted from May to July 2021. The obtained data were analyzed by using multinomial logistic, linear regression, and descriptive analysis. The results showed that 26.4% of consumers were willing to pay for organic eggs 10% more than the current price. The factor that influenced WTP was product quality. Meanwhile, the factors that influence the price were the eggs taste and the organic label. The results showed that market players of organic egg agribusiness still have the opportunity to increase the price of organic eggs. However, they must inform consumers about the health benefits of organic eggs and include them on the organic eggs label.